Analytical solutions for nonlinear systems using Nucci's reduction approach and generalized projective Riccati equations - Yepez-Martinez, Huitzilin; Hashemi, Mir Sajjad; Alshomrani, Ali Saleh; İnç, Mustafa (Amer Inst Mathematical Sciences-Aims, 2023)
In this study, the Nucci's reduction approach and the method of generalized projective Riccati equations (GPREs) were utilized to derive novel analytical solutions for the (1+1) -dimensional classical Boussinesq equations, the generalized reaction Duffing model, and the nonlinear Pochhammer-Chree equation. The nonlinear systems mentioned earlier have been solved using analytical methods, which impose certain limitations on the interaction parameters and the coefficients of the guess solutions. However, in the case of the double sub-equation guess solution, analytic solutions were allowed. The soliton solutions that were obtained through this method display real positive values for the wave phase transformation, which is a novel result in the application of the generalized projective Riccati method. In previous applications of this method, the real positive properties of the solutions were not thoroughly investigated.
Keywords: the Nucci's reduction method; the generalized projective Riccati equations method; the (1+1)-dimensional classical Boussinesq equations; the generalized reaction duffing model; the nonlinear Pochhammer-Chree equation; traveling wave solutions